2020
DOI: 10.1101/2020.06.23.166181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of genetic, transcriptomic, and clinical data provides insight into 16p11.2 and 22q11.2 CNV genes

Abstract: Deletions and duplications of the 16p11.2 and 22q11.2 copy number variant (CNV) regions are associated with brain-related disorders including autism spectrum disorder, schizophrenia, bipolar disorder, obesity, and intellectual disability. The contribution of individual genes in each CNV to each phenotype is unknown. We propose a novel in silico approach to systematically interrogate each gene's effect on brain-related disorders. As CNVs affect RNA copy number, we attempted to fine-map each CNV region by asking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 133 publications
(287 reference statements)
1
7
0
Order By: Relevance
“…Moreover, in addition to KCTD13, Orgo-Seq prioritizes 2 other candidate driver genes in the 16p11.2 locus (YPEL3 and INO80E) in neuroepithelial cells. A recent report showed evidence for these 2 genes as candidate schizophrenia-associated genes in the locus using a large biobank 48 , which further reaffirms our finding using Orgo-Seq that there is unlikely to be a single driver gene in the 16p11.2 locus.…”
Section: Evidence For the Role Of Multiple Driver Genes In The 16p11supporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, in addition to KCTD13, Orgo-Seq prioritizes 2 other candidate driver genes in the 16p11.2 locus (YPEL3 and INO80E) in neuroepithelial cells. A recent report showed evidence for these 2 genes as candidate schizophrenia-associated genes in the locus using a large biobank 48 , which further reaffirms our finding using Orgo-Seq that there is unlikely to be a single driver gene in the 16p11.2 locus.…”
Section: Evidence For the Role Of Multiple Driver Genes In The 16p11supporting
confidence: 88%
“…Among our top 3 candidate genes in the 16p11.2 locus, two of the genes (YPEL3 and INO80E) were recently reported to be associated with schizophrenia through an association study of imputed gene expression with 5 medical traits identified from electronic health records for over 3 million individuals 48 . In Ypel3 -/mice, an association with absence of startle reflex (P=2.2×10 -5 ) and an association with short tibia (P=5.1×10 -6 ) had been reported 49 .…”
Section: Cell Type Specific Co-transcriptional Network Modeling Can Pmentioning
confidence: 99%
“…With this enhancement, we find one 22q11.2 gene ( PPIL2 ) significantly associated with schizophrenia at a permutation-based threshold (Table 1, Supplementary table 5). We note that the permutation-based threshold is less conservative than the experiment-wide thresholds used in previous analysis [22]. However, we can identify five top genes at 22q11.2 associated with BMI ( YDJC, CCDC116, PPIL2, THAP7, UBE2L3 ), primarily located outside the canonical CNV region (LCR D-E), three with bipolar disorder ( TMEM191B, TUBA8, PPIL2 ), six with ASD ( CLTCL1, AC004471.10, UFD1L, DGCR14, CCDC188, DGCR9 ), and two with IQ ( SEPT5, LINC00896 ) (Table 1, Supplementary table 5).…”
Section: Resultsmentioning
confidence: 99%
“…We included noncoding genes, as they have not received significant attention in studies of these regions, despite some evidence of miRNA contribution to 22q11.2 phenotypes. In addition, we considered flanking genes within 200kb of the region, as there is suggestive evidence of broader transcriptional effects in CNV carriers, and because we previously found evidence of flanking gene involvement in psychosis [22,27]. Supplementary tables 1 and 2 contain single and pairwise CNV genes used in analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These include, for example, SEZ6L2 (synapse numbers, dendritic morphology, and neuritogenesis) (Qiu et al, 2021; Yaguchi et al, 2017), CORO1A (filopodia formation, required for initial neurite formation) (Alvarez Juliá et al, 2016; Dent et al, 2007), DOC2A (spontaneous neurotransmission associated with its calcium-dependent translocation) (Courtney et al, 2018; Groffen et al, 2006), TLCD3B (altered composition and levels of sphingolipids and glycerolipids associated with cellular membranes leading to synaptic protein mislocalization) (Tomasello et al, 2021), TAOK2 (brain size, neural connectivity and excitatory transmission) (Richter et al, 2019); PRRT2 (neuronal excitability) (Fruscione et al, 2018); and MAPK3 (dendritic alterations of cortical pyramidal neurons) (Blizinsky et al, 2016). Recently, integration of genetic regulation of gene expression with genome-wide association data from human cohorts pointed to INO80E as the potential driver of schizophrenia due to 16p11.2 duplication and to both SPN and INO80E as contributors to the increased body mass index due to 16p11.2 deletion (Vysotskiy et al, 2021). Other model studies have also pointed to interaction between 16p11.2 genes as potentially being responsible for abnormal phenotypes (Iyer et al, 2018; McCammon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%